2018
DOI: 10.1021/jacs.8b10288
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, Lewis Base-Catalyzed Carbosulfenylation of Alkenylboronates by 1,2-Boronate Migration

Abstract: A catalytic, enantioselective method for the preparation of chiral, non-racemic, alkylboronic esters bearing two vicinal stereogenic centers is described. The reaction proceeds via a 1,2-migration of a zwitterionic thiiranium–boronate complex to give exclusively anti carbosulfenylation products. A broad scope of aryl groups migrate with good yield and excellent enantioselectivity (up to 99:1 e.r.). Similarly, a range of di- and trisubstituted alkenylboronic esters are competent reaction partners. This method p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 32 publications
0
32
0
2
Order By: Relevance
“…[121] Denmark et al have recentlyp ublished ar eport on the transition-metal-free enantioselective carbosulfenylation of alkenyl boronates to afford b-sulfur secondaryo rt ertiary alcohols after oxidation (Scheme 28c). [122] The aforementioned substrates, tetracoordinated alkenyl boronate complexes, have also been employed in radical chemistry.S tuder et al [123] and Aggarwal et al, [124] independently,a nd later Renaud and co-workers, [125] have shown that the vinyl boronate complexes are efficient radical acceptors, and the radicala nion adducts undergo 1,2-alkyl/aryl shifts from boron to carbon,t hus leading to av ariety of synthetically useful products (Scheme 29a). This method has been applied by Aggarwal's group with heterocycles such as furan or indole to give 2,5-disubstituted furanso r2 ,3-disubstituted indoles (Scheme29b).…”
Section: Applications Of Alkenyl Boronatesmentioning
confidence: 99%
“…[121] Denmark et al have recentlyp ublished ar eport on the transition-metal-free enantioselective carbosulfenylation of alkenyl boronates to afford b-sulfur secondaryo rt ertiary alcohols after oxidation (Scheme 28c). [122] The aforementioned substrates, tetracoordinated alkenyl boronate complexes, have also been employed in radical chemistry.S tuder et al [123] and Aggarwal et al, [124] independently,a nd later Renaud and co-workers, [125] have shown that the vinyl boronate complexes are efficient radical acceptors, and the radicala nion adducts undergo 1,2-alkyl/aryl shifts from boron to carbon,t hus leading to av ariety of synthetically useful products (Scheme 29a). This method has been applied by Aggarwal's group with heterocycles such as furan or indole to give 2,5-disubstituted furanso r2 ,3-disubstituted indoles (Scheme29b).…”
Section: Applications Of Alkenyl Boronatesmentioning
confidence: 99%
“…The semipinacol rearrangement of allylic alcohols has become a powerful strategy for the formation of a variety of β‐functionalized carbonyl compounds with an α‐quaternary carbon center . Although numerous catalytic enantioselective variants have been documented, to the best of our knowledge, no example of a catalytic asymmetric sulfenylation/semipinacol rearrangement reaction of allylic alcohols has been reported . Herein, we present the development of a catalytic asymmetric sulfenylation/semipinacol rearrangement reaction of 1,1‐disubstituted and trisubstituted allylic alcohols.…”
Section: Figurementioning
confidence: 99%
“…[12] Although numerous catalytic enantioselective variants have been documented, [13] to the best of our knowledge,n oe xample of ac atalytic asymmetric sulfenylation/semipinacol rearrangement reaction of allylic alcohols has been reported. [14] Herein, we present the development of ac atalytic asymmetric sulfenylation/semipinacol rearrangement reaction of 1,1-disubstituted and trisubstituted allylic alcohols.This process provides astraightforward and efficient method to synthesize aw ide range of b-arylthio ketones containing an all-carbon quaternary center (Scheme 1c). To realize this reaction, ac atalytic system containing ac hiral Lewis base and ac hiral Brønsted acid is required to activate the sulfenylating agent for the enantioselective formation of thiiranium ion intermediates.…”
mentioning
confidence: 99%
“…Catalytic electrophilic thiolation reactions provide a facile and straightforward route for the transformation of alkenes and alkynes into sulfur-containing molecules. [18][19][20][21][22][23] In the past few years, considerable efforts have been devoted to the development of catalytic enantioselective versions of this reaction. Particularly, by chiral chalcogenophosphoramide [19,21] and chiral bifunctional chalcogenide catalysis, [22] a range of chiral sulfur-containing compounds could be prepared efficiently.…”
mentioning
confidence: 99%